Analisis Perbandingan Sistem Pendukung Keputusan Pemilihan Media Sosial Sebagai Sarana Promosi Di Tembilahan - Aji, Muhammad Syah Jihan; Ilyas (Indra Institute Research & Publication, 2023)
With the rapid development of technology at this time, internet services cannot be separated from everyday human activities. the many conveniences of using internet services make people involve internet services in doing business online using social media services. Business competition is also one that must be faced by creative economy actors. With competitors or competitors making similar products increasing, while products that are made are less well known to consumers, creative businesses cannot reach market segments effectively. Some of the social media that are most often used to carry out online buying and selling activities are: Facebook, Twitter, Instagram, WhatsApp, Tiktok, and others. The application of the Decision Support System uses the SAW and TOPSIS methods in selecting the best social media as a means of promotion, and choosing which method is most appropriate for determining social media as a means of promotion in Tembilahan. The SAW method is the most relevant in solving this case and the Facebook alternative is chosen as a good and effective social media to be used as a promotional medium.